Flexural performance of FRP-reinforced concrete encased steel composite beams - Kara, İlker Fatih (Techno-Press, 2016)
This paper presents a numerical method for estimating the curvature, deflection and moment capacity of FRP-reinforced concrete encased steel composite beams (FRP-RCS). A sectional analysis is first carried out to predict the moment-curvature relationship from which beam deflection and moment capacity are then calculated. Comparisons between theoretical and experimental results of tests conducted elsewhere show that the proposed numerical technique can accurately predict moment capacity and deflection of FRP-RCS composite beam. The numerical results also indicated that beam ductility and stiffness are improved when encased steel is added to FRP reinforced concrete beams. ACI, ISIS and Bischoff models for deflection prediction compared well at low load, however, significantly underestimated the experimental results for high load levels.
Keywords: fiber reinforced polymers; deflection; ductility; concrete; encased steel beam